Bi and multivariate diagnosis of nutrient imbalance in brinjal (Solanum melongena) - RAGHUPATHI, H B; BHARGAVA, B S (The Indian Journal of Agricultural Sciences, 2013)
A survey involving collection of leaf samples was conducted during 1996 in brinjal (Solanum melongena L.)fields to develop diagnostic norms and for identification of yield limiting nuturients. The leaf nutrient status wasinterpreted using diagnosis and recommendation integrated system and compositional nutrient diagnosis. The correlationshucture among the nutrients was extracted by principal component analysis. The 4 principal components explainednearly 65% of the total variation and the designated principal components were (N+P+Mg+Fe-Mn-), (P-CaMg+S-Zn+),(N-K-Ca+Fe-) and (K-Fe+). Nitrogen was identified as the most common yield limiting nutrient in thelow yielding popUlation.